Non-linear effects of corporate global value chain participation on pollution emissions: evidence from China - Wang, Bo; Shao, Xuyang; Xu, Honghai (Frontiers in Energy Research, 2023)
Global value chains (GVCs) involve production and distribution cooperation as well as pollution redistribution. With the increasing frequency of global trade activities and the growing problem of environmental pollution, the impact of GVC participation on environmental pollution has attracted considerable academic attention. In this study, a dynamic panel Gaussian mixture model was constructed using data from several databases, including Chinese industrial enterprise pollution emission and customs data from 2005 to 2013. We found that the degree of GVC participation of enterprises and pollution emission show a non-linear inverted U-shaped relationship. This indicates that the pollution emissions of enterprises increased and then decreased as the degree of GVC participation increased. We constructed separate models for the effects of output upstreamness and input downstreamness on pollution emissions and found that upstreamness is negatively related to pollution emissions, with the upstream economic components of GVC (such as technology research and development, international marketing, and key component manufacturing) producing emission reduction effects. Downstreamness, on the other hand, is positively correlated with emissions, which means that the downstream economic components of the GVC (e.g., processing, assembly, and production of non-critical components) will increase emissions. Based on the second finding, we proposed that the inverted U-shaped relationship is the result of the combined influence of upstream and downstream participation and confirmed this hypothesis by constructing a multiple mediating effects model. This study will help enterprises consciously implement environmental protection measures and broaden the scope of research on the environmental impact of GVCs, providing a broader segmented research perspective on the degree of participation in GVCs and the environmental performance of exporting enterprises, and guiding governments to formulate more effective industrial policies for foreign trade and promote better environmental performance of enterprises.